Production and marketing constraints of fisherwomen self help groups in Thoothukudi District, Tamil Nadu - Jayaraman, R. (Indian Journal of Fisheries, 2017)
A study was conducted to identify the constraints faced by fisherwomen self help groups (SHGs) especially with respect to production and marketing. A sample of 40 fisherwomen from the SHGs in Tharuvaikulam fishing village in Thoothukudi District of Tamil Nadu was selected randomly and the required data were collected using a pre-tested interview schedule in the year 2013. Garrett ranking technique was used to analyse the constraints ranked by the fisherwomen according to their perception of importance. Seven production constraints were identified and among them, high cost of inputs (raw material) was ranked first. They identified five financial constraints, of which lack of funds for starting and running business activities was the single most important constraint. Among the five constraints that influenced cohesion of the SHGs, lack of leadership and guidance affected the performance of the SHGs including their business activities. Among the 14 marketing constraints identified, lack of marketing skills was found the most important. With regard to performance constraints, it was observed that less profits brought down their performance. Among the six extension constraints that affected market access, lack of contact between producer and consumer was identified as most important. Lack of lateral thinking and innovation among the seven entrepreneurship constraints, was identified to deny them success in their business.